Does Having a Living Child Increase Women’s Risk of Intimate Partner Violence? Evidence from 2008- 2013 Nigeria Demographic and Health Surveys - Solanke, Bola Lukman; Ilevbare, Femi Monday (European Scientific Journal, ESJ, 2017)
This study examined the relationship between number of living children and intimate partner violence. This was with the view to ascertaining whether having living children or not having a living child was associated with increased risk of intimate partner violence among currently married women in Nigeria. The study analyzed data from 2008-2013 Nigeria Demographic and Health Surveys. The binary logistic regression was applied. Results showed that women who had two or more living children were 20.5% more likely to experience intimate partner violence compared with women who had no living child (OR=1.205; CI: 0.993-1.461). The study concluded that having living children increase women’s risk of intimate partner violence in Nigeria. Women experiencing intimate partner violence should seek psychosocial counselling to reduce the incidence of intimate partner violence that may arise from childbearing.